Industrial location in the United States : an economic analysis - Burrows, James C.; Metcalf, Charles E.; Kaler, John B.; Charles River Associates (Lexington, Mass. : Heath Lexington Books, 1971)
This book presents a model or set of models of each area's of industrial structure.
"A Charles River Associates research study."
"Based on a study performed by the authors ... entitled Area employment prediction to determine public facilities requirements, prepared for the Economic Development Administration, U.S. Department of Commerce, Washington, D.C."
Includes bibliographical footnotes.
asm 23/01/2019
Loans
Keywords: Industrial location